2017
DOI: 10.3389/fphar.2017.00650
|View full text |Cite
|
Sign up to set email alerts
|

Development of a UPLC-FLD Method for Detection of Aflatoxin B1 and M1 in Animal Tissue to Study the Effect of Curcumin on Mycotoxin Clearance Rates

Abstract: Aflatoxin B1 (AFB1) and its metabolite aflatoxin M1 (AFM1) are well-known carcinogens for humans and animals health. In this study, an ultra-high performance liquid chromatography linked with fluorescence detection (UPLC-FLD) method was optimized and validated. In addition, we investigated for the first time, the influence of curcumin on residue depletion of AFB1 and AFM1 in liver, kidney, and muscle tissues of broiler chickens and estimated a necessary clearance time required for AFB1 and AFM1 residues. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Apart from being a hazard for the poultry industries and domestic animals, AFs are a critical public health threat, being responsible for Reyes syndrome and acute and chronic liver failure [ 12 ]. The metabolic and toxic effects of AFB1 and AFM1 are principally observed in the liver [ 13 15 ]; the lung might also be a target organ after exposures of inhalation and diet, and indeed evidences from both laboratory and epidemiologic study validate a carcinogenic effect of AFB1 on human lung tissue [ 16 , 17 ]. Moreover, several epidemiological studies implicate that AFB1 plays a role in the clinical incidence of gastroenteric tumors of Asians and Africans [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being a hazard for the poultry industries and domestic animals, AFs are a critical public health threat, being responsible for Reyes syndrome and acute and chronic liver failure [ 12 ]. The metabolic and toxic effects of AFB1 and AFM1 are principally observed in the liver [ 13 15 ]; the lung might also be a target organ after exposures of inhalation and diet, and indeed evidences from both laboratory and epidemiologic study validate a carcinogenic effect of AFB1 on human lung tissue [ 16 , 17 ]. Moreover, several epidemiological studies implicate that AFB1 plays a role in the clinical incidence of gastroenteric tumors of Asians and Africans [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported that they can lead to Reyes syndrome, neuropathy, respiratory diseases, renal injury, and liver damage [5,6]. The metabolic course of AFB1 and AFM1 are proved to be principally in the liver tissue [7,8,9]; lung and gastrointestinal tract are two other key targets which are susceptible to the carcinogenic effects of AFs [10,11,12]. AFB1 and AFM1 are also verified to be a pathogenic factor leading to underweight and hypoimmune young people [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In general, lack of fit test was employed to analyze the variation in the data around the fitted model [16]. Previous report demonstrated that proper preparation of samples gives good recovery results [17]. Ekberg et al (2008) demonstrated that choosing of an extraction solvent which is easily available and cheap plays a crucial role in optimization of an extraction process [18].…”
Section: Discussionmentioning
confidence: 99%